Observing the Observer: Freud and the Limits of Empiricism. (February 2017) - Allison, Elizabeth
Abstract : In Freud's representations of the origins of psychoanalysis he tended to deny the existence of any significant philosophical or literary precursors, preferring to present psychoanalysis as an empirical science. This paper will situate Freud's work in the context of the philosophical crisis resulting from David Hume's pushing of empiricism to its limits. The difficulties that Hume encountered in his attempt to observe the observer raised unsettling questions concerning the constitution of the psyche and its implications for the possibility of knowledge and agency that a succession of subsequent thinkers struggled to answer. Freud's work can fruitfully be seen as an intervention in this debate, which, as we shall see, is still ongoing.